2011
DOI: 10.1302/0301-620x.93b5.26214
|View full text |Cite
|
Sign up to set email alerts
|

Unnecessary contraindications for mobile-bearing unicompartmental knee replacement

Abstract: The contraindications for unicompartmental knee replacement (UKR) remain controversial. The views of many surgeons are based on Kozinn and Scott's 1989 publication which stated that patients who weighed more than 82 kg, were younger than 60 years, undertook heavy labour, had exposed bone in the patellofemoral joint or chondrocalcinosis, were not ideal candidates for UKR. Our aim was to determine whether these potential contraindications should apply to patients with a mobile-bearing UKR. In order to do this th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
143
0
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(159 citation statements)
references
References 28 publications
7
143
0
9
Order By: Relevance
“…Previous shorter term studies have also shown that patients treated with the mobile-bearing 258 UKR that have the proposed contra-indications have similar functional outcomes and survival 259 as those considered ideal [16,17]. This study has however shown that patients with contra-260 indications actually have better results.…”
Section: Groups 246mentioning
confidence: 66%
“…Previous shorter term studies have also shown that patients treated with the mobile-bearing 258 UKR that have the proposed contra-indications have similar functional outcomes and survival 259 as those considered ideal [16,17]. This study has however shown that patients with contra-260 indications actually have better results.…”
Section: Groups 246mentioning
confidence: 66%
“…In a study by Xing et al 21 with 178 patients, the outcome of UKA was not influenced by patient's age, BMI and early degeneration in the PFJ. Furthermore, the clinical outcome of the 1000 mobile-bearing UKA at a mean of 5.6 year in a prospective study by Pandit et al 22 was similar for both patients weighing less and more than 82 kg. Tabor et al 23 reported higher survivorship among obese patients compared with those who were not obese in a 20-year follow-up study of 82 patients.…”
Section: Discussionmentioning
confidence: 84%
“…Preoperative data including patient demographics as well as the patient's height and weight were recorded on dedicated databases. Data from centre 1 has already been used in a study of UKR on patients with weight above or below 82 kg and data from centre 2 has been used in a similar study with BMI above or below 32 13,16 .…”
Section: Methodsmentioning
confidence: 99%
“…More recent work, reviewing 40 fixed bearing UKRs with a BMI > 35, and a matched group with a BMI < 35, demonstrated higher revision rates in those with a BMI > 35 12 . Conversely, Pandit et al have shown that a weight > 82 kg was not associated with a higher failure rate using a mobile bearing UKR but they did not study the impact of BMI 13 .…”
Section: Introductionmentioning
confidence: 94%